Формирование нанопленок Cu, Ag, Au под воздействием атомов водорода - Жавжаров, Е.Л.; Матюшин, В.М. (Технология и конструирование в электронной аппаратуре, 2015)
Приведены результаты экспериментального исследования процесса получения металлических нанопленок Ag, Cu, Au в среде атомарного водорода. Предложено два метода, позволяющих контролируемо получать пленки металлов толщиной 1—20 нм при вакууме в камере порядка 20 Па. В основе этих методов лежит процесс распыления атомов поверхности твердого тела, возникающий под действием энергии рекомбинации атомарного водорода в молекулярный. Наведено результати експериментального дослідження процесу отримання металевих наноплівок Ag, Cu, Au в середовищі атомарного водню. Запропоновано два методи обробки, що дозволяють контрольовано отримувати плівки металів товщиною 1—20 нм при вакуумі в камері близько 20 Па. В основі цих методів лежить процес розпилення атомів поверхні твердого тіла, що виникає під дією енергії рекомбінації атомарного водню в молекулярний. Due to their electrical properties, thin metallic films are widely used in modern micro- and nanoelectronics. These properties allow solving fundamental problems of surface and solid state physics. Up-to-date methods of producing thin films involve high vacuum or multi-stage processes, which calls for complicated equipment. The authors propose an alternative method of producing thin metallic films using atomic hydrogen. Exothermal reaction of atoms recombination in a molecule (about 4.5 eV / recombination act) initiated on the solid surface by atomic hydrogen may stimulate local heating, spraying and surface atoms transfer. We investigated the process of atomic hydrogen treatment of Cu, Ag and Au metal films, obtained by thermal vacuum evaporation. There are two methods of obtaining nanofilms using atomic hydrogen treatment: sputtering and vapor-phase epitaxy. In the first method, a film is formed by reducing the thickness of the starting film. This method allows obtaining a film as thick as the monolayer. In the second method, a nanofilm is formed by deposition of metal atoms from the vapor phase. This method allows obtaining a film thickness from monolayer to ~10 nm. These methods allow creating nanofilms with controlled parameters and metal thickness. Such films would be technologically pure and have good adhesion.